Linear and Nonlinear Oblivious Data Hiding - Akansu Ali N; Ramkumar Mahalingam; Gang Litao (EURASIP Journal on Advances in Signal Processing, 2004)
The majority of the existing data hiding schemes are based on the direct-sequence (DS) modulation where a low-power random sequence is embedded into the original cover signal to represent hidden information. In this paper, we investigate linear and nonlinear modulation approaches in digital data hiding. One typical DS modulation algorithm is explored and its optimal oblivious detector is derived. The results expose its poor cover noise suppression as the hiding signature signal always has much lower energy than the cover signal. A simple nonlinear algorithm, called set partitioning, is proposed and its performance is analyzed. Analysis and simulation studies further demonstrate improvements over the existing schemes.